Analysis of Net Profit Margin, Current Ratio, and Total Assets Turnover to Assess Financial Performance at PT Kalbe Farma Tbk Period 2017-2021 - Sanjaya, Rudi; Puji rahayu, Krida; Lativa (Adpebi Science Series, 2022)
This study aims to determine the financial performance of PT Kalbe Farma Tbk. in 2017 to 2021, namely byanalyzing ratios in the form of profitability ratios whose indicators are Net Profit Margin, liquidity ratios usingCurrent Ratio, and activity ratios using Total Asset Turnover. This type of research is qualitative research withanalytical methods through the stages of secondary documents, namely obtaining data from the company's financialstatements. The results show that the profitability ratio using the Net Profit Margin fluctuates, although it tends toincrease but is still below the industry standard where the average Net Profit Margin obtained in 2017-2021 is11.92% and the industry standard is 20%. And the liquidity ratio using the Current Ratio has results that show veryhealthy financial performance, the average Current Ratio in 2012-2021 is above the industry standard of 441% or4.41 times where the industry standard is 200% or 2 times. The results of the activity ratio research using TotalAsset Turnover show an average result that is not good, which has an average yield of 1.10 times with the industrystandard 2 times. Thus, the financial performance of PT Kalbe Farma Tbk. the 2017-2021 period seen from theprofitability ratio using Net Profit Margin and the activity ratio using Total Asset Turnover, both of which are saidto be in poor financial performance. Meanwhile, the financial performance of PT Kalbe Farma Tbk. seen from theliquidity ratio using the Current Ratio is said to be in good condition.